2021
DOI: 10.3390/math9161954
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Passengers’ Satisfaction with the Light Rail Transit Service in Alpha Cities: Evidence from Kuala Lumpur, Malaysia Using Structural Equation Modelling

Abstract: Policy makers and service providers must have a good understanding of the determinants of passengers’ satisfaction with light rail transit (LRT) in order to be able to formulate effective strategies that ensure passenger satisfaction, which would in turn help to retain existing passengers and attract new ones. This is seen as the most important determinant of the long-term financial performance of LRT service. In this context, the present study seeks to establish the influence of passenger expectation, perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…Thus, clients not satisfied with the service would not be loyal to the service and would not recommend it to others [39]. Some papers have attempts to investigate the factors influencing the satisfaction of rail transit passengers based on the evidence from the light rail transit [40]. In this sense, it has been identified that an indicator of a successful public transport service is the number of passengers that the system is able to retain and attract [39,41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, clients not satisfied with the service would not be loyal to the service and would not recommend it to others [39]. Some papers have attempts to investigate the factors influencing the satisfaction of rail transit passengers based on the evidence from the light rail transit [40]. In this sense, it has been identified that an indicator of a successful public transport service is the number of passengers that the system is able to retain and attract [39,41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Kwan et al [4] stated that Kuala Lumpur had an 83% private transport use rate, while public transportation was used by 17%. Relying so extensively on private transport has several negative effects: environmental conditions and the quality of life are adversely impacted, while it also leads to busier roads, polluted air, noisy conditions, and traffic accidents [5][6][7][8][9]. According to Mouwen [8], transport is responsible for 40% of the emissions of carbon dioxide and over 70% of different pollutant types.…”
Section: Introductionmentioning
confidence: 99%
“…Public transport is an excellent alternative to solve these problems [6,[8][9][10]. Wall et al [11] and Ibrahim et al [12] noted that the use of sustainable modes of transportation-for instance, city center public transport systems-reduced traffic congestion and the emissions of CO 2 and NO X per mile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of social impact, the use of private motorised vehicles led to a reduction in personal safety and increase in accident risk, mental health problems, and excessive time spent during traffic congestion [5,[9][10][11]. In summary, trips performed via motorised vehicles were identified as among the most negative causes of the university ecological footprint [12,13].…”
Section: Introductionmentioning
confidence: 99%